2013
DOI: 10.4236/ojfd.2013.33025
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Hydrodynamic of Multihull Tunnel Vessel

Abstract: The research described in this paper was carried out to predict the numerical hydrodynamic of multihull tunnel vessel at various speeds. The hull form of vessel is fairly generated by the tunnel hull form generator (THFG) code using the Non Uniform Rational B-Spline (NURBS) method. Then, the hydrodynamic simulation of high speed vessel is carried out based on finite volume discretization method using volume of fluid (VOF) model to consider free surface between water and air phases around the vessel. A dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Several experimental and numerical studies have been conducted focusing on the performance of tunneled planing hulls. Ghassabzadeh et al numerically simulated the hydrodynamic performance of a multihull tunnel vehicle based on FLUENT software, and the results indicated that the accuracy was acceptable [9,10]. Chaney introduced a numerical model based on fully unsteady aerodynamic extreme-ground-effect theory and the hydrodynamic added-mass strip theory for tunnel hull vertical plane dynamics in wind gust and wave simulations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental and numerical studies have been conducted focusing on the performance of tunneled planing hulls. Ghassabzadeh et al numerically simulated the hydrodynamic performance of a multihull tunnel vehicle based on FLUENT software, and the results indicated that the accuracy was acceptable [9,10]. Chaney introduced a numerical model based on fully unsteady aerodynamic extreme-ground-effect theory and the hydrodynamic added-mass strip theory for tunnel hull vertical plane dynamics in wind gust and wave simulations [11].…”
Section: Introductionmentioning
confidence: 99%
“…They have presented the hydrodynamics of the planing hull using BEM to find pressure resistance, induced resistance, and many related to hydrodynamic characteristics [18,19,20,21,22]. Ghassabzadeh and Ghassemi employed a NURBS to design the hull of tunnel ships [23,24,25,26]. Also, many numerical results on the planing hull carried out by CFD solver [27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Reza Yousefi et al [2,7] changed the cougar highspeed mono-hull into a tunneled and succeeded to reduce the body drag by 14 % in the maximum speed of the hull. Making a multibody shell, Ghassabzade and Ghasemi [3,4] investigated the behavior of the hull in different speeds using numerical and experimental modeling. Hailong Shen et al [5] studied the catamaran hull behavior by means of the moving mesh method and compared the results obtained from two methods of Savitsky, and Mori Muljowidodo et al [6] made an attempt to design and simulate a trimaran planing hull (USV).…”
Section: Introductionmentioning
confidence: 99%